Software quality model for a research‐driven organization—An experience report. Issue 5 (12th October 2017) - Wolski, Marcin; Walter, Bartosz; Kupiński, Szymon; Chojnacki, Jakub
Abstract: In the paper, we present a measurement framework for evaluating quality in software products developed within the research and innovation framework project GÉANT. The proposed framework is based on the quality models by Boehm and McCall, but also addresses the presence and point of view of a third stakeholder: an external funding agency (EU), which has started and is temporally financing the project, but aims at making it self‐financing in the future. We also provide results of evaluation of 2 projects from the GÉANT ecosystem and one open‐source system with this framework. Abstract : We propose a hierarchical quality evaluation framework. It is customized to the needs of innovative projects by identification of external funding agency, an additional stakeholder in the system. The framework is supplied with data coming from various sources.